2009
DOI: 10.1519/jsc.0b013e31818efbb2
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Ankle, Knee, and Hip Torque Production in Individuals With Chronic Ankle Instability

Abstract: There is some debate in the literature as to whether strength deficits exist at the ankle in individuals with chronic ankle instability (CAI). Additionally, there is evidence to suggest that knee and hip performance is altered in those with CAI. Therefore, the purpose of this study was to determine whether CAI is associated with deficits in ankle, knee, and hip torque. Fifteen subjects with unilateral CAI and fifteen subjects with healthy ankles participated. Subjects reported to the laboratory for one session… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
97
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(105 citation statements)
references
References 14 publications
6
97
0
2
Order By: Relevance
“…Several groups [12][13][14][15][16] have reported alterations in kneejoint kinematics, neuromuscular control, and knee torque production in those with CAI. Most recently, Terada et al 12 demonstrated altered feed-forward patterns of the vastus medialis oblique (VMO) muscle in those with CAI.…”
mentioning
confidence: 99%
“…Several groups [12][13][14][15][16] have reported alterations in kneejoint kinematics, neuromuscular control, and knee torque production in those with CAI. Most recently, Terada et al 12 demonstrated altered feed-forward patterns of the vastus medialis oblique (VMO) muscle in those with CAI.…”
mentioning
confidence: 99%
“…Assessing balance remains a useful clinical tool as it can be measured over time to show changes and has been found to be useful in assessing deficits in those with CAI when compared to healthy individuals. Gribble et al [59][60][61] has reported proximal changes in subjects with CAI during walking, jump landing and dynamic balance tasks. These changes were hypothesized to occur following changes to the ankle joint due to centrally mediated changes in neuromuscular function [25,50].…”
Section: Sensorimotor Function and Ankle Instabilitymentioning
confidence: 99%
“…Previous studies have identified alterations in gait initiation and termination, 16,17 proximal adaptations in muscle strength and activation, 18,19 and proximal changes during functional tasks such as jump landing. 20 Cumulatively, these studies point toward the possibility that central changes in sensorimotor function are responsibility for alterations in movement.…”
mentioning
confidence: 99%